Global Trends and Research Fronts in Herbal Medicine for Male Infertility: A 20-Year Bibliometric and Visualized Analysis - Saddam Muhdi; Frida Septiani Tavia; Fala Mahfariansa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Male infertility represents a major global health concern, with oxidative stress playing a central role in the deterioration of sperm quality. In recent years, growing attention has been directed toward herbal medicine as a potential alternative or complementary therapy due to its antioxidant and multi-target properties. However, a comprehensive long-term overview of the global research landscape in this field remains limited. A bibliometric and visualized analysis was conducted using publications indexed in the Scopus database from 2005 to 2025. Eligible peer-reviewed articles were retrieved following PRISMA guidelines. Bibliometric indicators were analyzed using Biblioshiny (R-Bibliometrix) to assess publication trends, leading contributors, and thematic evolution, while VOSviewer was employed to visualize international collaboration networks, co-citation patterns, and keyword co-occurrence clusters. A total of 562 articles were included, revealing a strong upward trend in scientific output, particularly after 2016, with an annual growth rate of 15.78% and a peak in 2025. Iran, China, and Nigeria emerged as the most productive countries, while the Faculty of Veterinary Medicine and several universities in Africa, the Middle East, and Asia were identified as leading institutions. Keyword analysis highlighted three dominant research fronts: semen quality assessment, testicular histopathology, and oxidative stress–related molecular mechanisms. The collaboration network indicated increasing global and South–South research synergy. The field of herbal medicine for male infertility has evolved into a mature and multidisciplinary research domain, increasingly grounded in mechanistic and experimental evidence. These findings provide a strategic overview of research hotspots and emerging trends, offering valuable guidance for future experimental and clinical investigations.